Problem Based Learning dalam Pembelajaran Fiqih: Upaya Meningkatkan Hasil Belajar dan Keterlibatan Siswa MA Ismailiyah Ngusikan Jombang - Puput Dwi Wahyunita; Rohmat Hidayat; Lintang Ramadhani (YASIN, 2026)
Although the Problem Based Learning (PBL) model has been widely studied as an innovative learning strategy, research that specifically discusses its implementation and impact on Fiqh learning outcomes at the Madrasah Aliyah level, particularly on the topic of funeral rites, remains limited. This study aims to explain the implementation of the PBL model, determine the improvement in learning outcomes, and identify the supporting and inhibiting factors in its application in the Fiqh subject at MA Ismailiyah Ngusikan Jombang. This study used a qualitative approach with a Classroom Action Research design conducted in two cycles, involving 12 tenth-grade students as the research subjects. Data were collected through observation, interviews, tests (pretest and posttest), and documentation, and were then analyzed using a comparative descriptive technique to compare the results across cycles. The results showed that the implementation of the Problem Based Learning model was able to significantly improve students’ learning outcomes, with the average score increasing from 52.5 in the pre-cycle to 70 in Cycle I and 83.3 in Cycle II. Classical learning completeness also increased from 8.3% to 91.6% at the end of Cycle II. These findings contribute to strengthening constructivist and cognitive theory, while also expanding understanding of the effectiveness of problem-based learning in the context of Islamic religious education. This study concludes that the teacher’s role as a facilitator and the use of contextual problems are important factors in improving Fiqh learning outcomes, and also underscores the need for educators’ creativity in designing problem-based learning to support the improvement of learning quality in madrasah.